Diáspora negra, bruxaria e a demonização do "outro" : as raízes de Tituba "Eu, Tituba, bruxa negra de Salém" de Maryse Condé - Soares, José Leonardo dos Santos (2024)
Whether in children's imaginations or in religions, witchcraft has appeared in multiple forms over the centuries. Tituba, a historical character who was accused of witchcraft during the period known as the Salem witch hunt in the United States in the 17th century, was a black slave taken into a Puritan context and barely mentioned in official records. Maryse Condé fictionalizes the life of this character in Eu, Tituba, Bruxa Negra de Salém (1986), complementing the story with her own vision, emphasizing a black protagonist. This paper aims to investigate the arc of the character Tituba in the plot of the work in question from the perspectives of gender and black culture, exploring and relating the processes of alterity and subalternity present in the narrative, as well as rescuing the historical figure of the protagonist. Following the thesis that the perspectives show that the categories of race, ethnicity and nationality influence and impact on the decisions made and the impositions suffered by the character. To support the research, we will look at Russell and Alexander (2019) with regard to the history of witchcraft, Zordan (2005) when writing about the emblematic figure of the witch, the black diaspora by Paul Gilroy (1993), cultural identity discussed by Stuart Hall (2006), thinking about a decolonial feminism: Oyérónké Oyéwúmí (2004), as well as Condé's autobiographical work (1999) to better understand the motivations and the process of writing her works. The book "I, Tituba: Black Witch of Salem" offers an enlightening insight into the condition of women during the period when Puritan morals dominated society. Women were subjugated to the patriarchy exercised by the men in their families and by the Church. African women and their descendants faced even greater subordination, imposed by their masters and mistresses. Throughout the story, Tituba, despite all the adversities, persists and maintains her humanity, including the expression of desires and pleasures, which defy Christian morality. The narrative highlights Tituba's cultural wisdom and her connection with ancestors and spiritual forces. In this way, Maryse Condé blends history and fiction, filling in gaps in the story with her imagination.